Soybean Whey Bio-Processed Using Weissella hellenica D1501 Protects Neuronal PC12 Cells Against Oxidative Damage - Yin, Liqing; Zhang, Yongzhu; Azi, Fidelis; Tekliye, Mekonen; Zhou, Jianzhong; Li, Xiaonan; Xu, Zhuang; Dong, Mingsheng; Xia, Xiudong (Frontiers in Nutrition, 2022)
Soybean whey, as a byproduct of soybean industry, has caused considerable concern recently because of its abundant nutrients. To further utilize soybean whey, it was fermented with Weissella hellenica D1501 and the neuroprotective potency of this beverage were studied in the present work. The phenolic profile and antioxidant capacity of fermented soybean whey (FSBW) were analyzed. The neuroprotective effects were evaluated based on the hydrogen peroxide-stimulated oxidative damage model in a neural-like cell (PC12). Results demonstrated that soybean whey's phenolic contents and antioxidant activities markedly improved after fermentation. Glycoside isoflavones were efficiently converted into aglycones by W. hellenica D1501. FSBW extract apparently increased cell viability, decreased reactive oxide species levels, and protected antioxidant enzymes in oxidative damage. Furthermore, FSBW effectively reduced apoptosis rate through inhibition of Bax protein and improvement of Bcl-2 and Bcl-xL proteins. FSBW ameliorated cell cycle through decrease of p21 protein and increase of cyclin A protein. The findings of this study thus suggested that W. hellenica D1501-fermented soybean whey could protect nerve cells against oxidative damage.